Omissão de cuidados de enfermagem na pandemia da covid-19 - Nishiyama, Juliana Aparecida Peixoto (2022)
To analyze the omission of nursing care in the hospital context during the COVID-19 pandemic. Method: Cross-sectional study. It was developed in eight public units of a medium-sized university hospital in the Midwest region of Brazil. A sample of 98 nursing professionals (nurses and nursing technicians) consisted of 98 nursing professionals. Data collection was carried out by the researcher between August 2020 and March 2021. The validated instrument MISCARE-BRASIL was applied. Due to the COVID-19 pandemic, data collection was carried out in two ways: remotely, using the Google Forms® platform, WhatsApp® mobile application and email; and later on-site. The printed data were unified and in electronic media in electronic spreadsheets. After that, a descriptive and inferential statistical analysis was performed using the Statistical Package for Social Sciences® (SPSS) software, version 21.0. Large and medium companies were on measures of central attention as and median; and dispersion, as standard deviation (SD) interquartile range (IQR), minimum and maximum. Categorical variables absolute frequency (n) and percentages (%). An inferential analysis was performed using the Mann-Whitney U test for comparisons of up to two groups and Kruskal-Wallis for more than two data, considering an asymmetric distribution of those verified by the Shapiro-Wilk test.The significance level adopted in the evaluations was 5%, expressed in the significance comparisons when p-value ≤ 0, 05. The internal consistency of MISCARE-BRASIL was measured by Cronbach's alpha (α), followed by internal consistency α=0.88 for part A and α=0.93 for part B of the instrument. The study was approved by the Research Ethics Committee, under opinion nº. 3.181.185/2019, CAAE: 07626019.5.0000.5541 and amendment nº. 4,113,128. Results: The results were obtained without two scientific format. The first identifies the omitted ones and the prevalence of the reasons of omission of nursing care during the COVID-19 pandemic. The most omitted care were airway aspiration (3.39±1.61) and participation in the interdisciplinary team discussion (3.26±1.19). The least omitted were checking capillary blood glucose (4.79±0.45) and hand hygiene (4.75±0.43). The initial number of personnel, materials/equipment was the prevalent reason for omission (83.7%). The second article verifies the omission of nursing care according to the elements of hospital work organization. Workers do not intend to work (5.9%) and are with work (52%) and with the team (53.1%). They reported that the nursing staff at the unit was present around 7% of the time (42.9%). In comparisons, the largest unit of nursing care, which was interpreted as the smallest omission. The smaller unit sector had as a reference (plus the mission) the accommodation set (106.6). Nurses showed significantly greater omission of care than nursing technicians/assistants with complete records in the medical records (2.88±0.036), medication administration (3.03±0.032), patient hygiene (3.03± 0.016) and care with venous access (3.18±0.011). Also by comparison, the six-hour shift had more omissions than the 12-hour or rotating shifts with oral care (2.60±0.44), patient and/or family planning and hygiene for discharge within (2.62±0.44), answering the patient's call takes five minutes (2.86±0.43) and requests for the administration of prescribed medications (if necessary) are answered in fifteen minutes (3.05±0.43). Conclusion: During the COVID-19 pandemic, important nursing care for the patient was omitted. As reasons and prevalence of omission of nursing care are related to the necessary number of humans and materials/equipment. In addition, the study indicated that the organization of hospital work was related to the omission of nursing care, it does not concern hospital sectorization, professional hierarchy and organization of shift work. Therefore, it is important that nursing leaders and institutional management pay attention to working conditions in order to mitigate the omission of care.